Organization's perspective of managing B2C e-Commerce implementation: Lessons from fashion and apparel business in Malaysia - Paris D.L.; Bahari M.; Iahad N.A.; Hashim H.; Ismail W. (IEEE Computer Society, 2024)
This paper proposes an organization's perspective of the business-to-customer (B2C) e-Commerce system implementation framework in Malaysian fashion and apparel business. The framework was developed based upon two in-depth case studies which were conducted in two fashion and apparel business in Malaysia. From the cross-cases, ten implementation factors (with its characteristics) that pertinent to the stages of Kotter's model have emerged. This includes factors of financial structure, e-Commerce compatibility, marketing strategy, customer analysis, e-Commerce relative advantages, rewards, e-Commerce maintenance, employee training, and e-Commerce re-engineering. Additionally, three implementation actors - e-Commerce champion, system moderator and vendor, involved in the respective stages of the implementation process. Finding of this study suggests that all the ten factors and the three implementation actors are the ingredients that organizations should not be overlooked when B2C e-Commerce implementation initiative is considered. 2017 IEEE.